(untitled) (Global Journal of Science Frontier Research, 2022)
Science progresses slowly by Apollonian, who extends its boundary by bringing perfection on the established lines. Science often takes an intuitive leap by Dionysian, who opens an unexpected new line of research. The present paper presents twelve mixes of such ideas which together are capable of extending the scope of science. An analyst could find several ideas within one main idea; assumption, imagination, intuition or obvious reality, not one, however, on any beaten track. Each of the main idea is supported by a figure, the mind’s artwork, captioned with several new ideas. Most of the ideas have a bias towards operational consciousness. The erected framework has the potential of ushering in a new Multiversal Worldview accommodating science, humanities, and spirit together.